Comparison of a PWM inverter and a multilevel inverter using the switching function analysis for harmonic content and efficiency - Paterakis, Fotis; Marouchos, Christos; Darwish, Mohammed K.; Nafpaktitis, Drosos (My University, 2017)
A conventional 3-level PWM Inverter and a Cascaded Multilevel Inverter, both rated at 230Vrms voltage output and 3KW are analysed using the Switching Function. The PWM signal for the 3-level inverter is derived by applying the Switching Function Technique to the equal area principle. For the Cascaded Multilevel Inverter the Switching Function Technique is initially applied to each H-bridge, and then added to derive the overall Switching Function for the Multilevel Inverter output. A new technique is employed to derive the pulse width of each H-bridge converter in order to construct the output voltage. Voltage expressions of the output voltages are derived for both topologies. The switching frequency is chosen to be the same for both inverters. To ensure the same number of commutations over a fundamental cycle for both inverters, the levels of the Multilevel Inverter must be properly selected to meet the PWM frequency of the conventional inverter. Frequency spectrum and expressions of THD of the output voltage are derived. The two inverters are compared in terms of THD and harmonic content of the output voltage. The efficiency is concluded from the number of switching instances and other parameters of the circuit.
Keywords: Equal areas; Multilevel inverter; PWM; Switching function; THD